Answer:
x = - 5, x = 4
Step-by-step explanation:
Given
f(x) = x² + x - 20
To find the zeros equate f(x) to zero, that is
x² + x - 20 = 0
Consider the factors of the constant term ( - 20) which sum to give the coefficient of the x- term ( + 1)
The factors are + 5 and - 4, since
5 × - 4 = - 20 and + 5 - 4 = + 1, hence
(x + 5)x - 4) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 5 = 0 ⇒ x = - 5
x - 4 = 0 ⇒ x = 4
Answer:
The zeroes are {-5, 4}.
Step-by-step explanation:
f(x) = x^2 + x - 20 = 0
To factor this function we need 2 numbers whose sum is + 1 ( x = 1x) and whose product is -20. They are 5 and - 4 so we have:
(x + 5)(x - 4) = 0
x + 5 = 0 gives x = -5
and x - 4 = 0 gives x = 4.
what is the constant variation of k, of the direct variation, y=kx, through (5,8)
Answer:
The constant of variation is 1.6.
Step-by-step explanation:
y = kx and x = 5 when y = 8 and k = the constant of variation.
8 = k*5
k = 8.5 = 1.6.
Answer:
8/5
Step-by-step explanation:
Plug in the point given into
y=kx.
The number you get for y will be your constant of variation, also know as constant of proportionality.
(x,y)=(5,8) implies 8=k(5)
So in solving that equation we just need to divide both sides by 5 giving us:
8/5=k.
The area of the rectangle is
square inches.
Answer:
42
Step-by-step explanation:
all I did was multiply 6 by 7 and i got 42
Gabriel Is making a mixture of compost and soil to use for a special plant. He wants his Final mix to be two parts compost to 10 parts potting soil. he wants to end up with 6 kg of mix. How many kg of compost should Gabrial use?
well, so we know the ratio of compost to soil is 2 : 10, or namely 2/10 which simplifies to 1/5 or namely the ratio of 1 : 5.
the mix will be 6 kgs total, so we'll simply divide the whole amount by (1 + 5), the sum of the ratios, and then distribute accordingly.
[tex]\bf 2:10\implies 1:5\qquad \qquad \cfrac{compost}{soil}\qquad \cfrac{1\cdot ~~\frac{6}{1+5}~~}{5\cdot \frac{6}{1+5}}\implies \cfrac{1\cdot 1}{5\cdot 1}\implies \cfrac{\stackrel{compost}{\boxed{1~kg}}}{5~kg}[/tex]
Answer:
Gabriel Is making a mixture of compost and soil to use for a special plant. He wants his Final mix to be two parts compost to 10 parts potting soil. he wants to end up with 6 kg of mix. How many kg of compost should Gabriel use?
Step-by-step explanation:
We have a total of 12 parts, where 2 are compost, and on the other hand 6 kg which is the total of the whole mixture, divided by 12; 6/12 = 0.5 would be each of the parts, we multiply it by 2; 0.5 x 2 = 1 kg would be the part of compost, and 0.5 x 10 = 5 kg would be the part of potting soil which added, gives us the total 6 kg.
Mr.Rector bought an 8-ounce bottle of juice. He accidentally knocked it over and spill 1/4 of the juice. How many ounces of juice does she have left to quench his thirst?
Answer:
6 oz
Step-by-step explanation:
If he spilled 1/4 of the juice, then he has 3/4 of the original volume left.
(3/4)(8 oz) = 6 oz.
He has 6 oz left to enjoy.
Like terms can be added or subtracted true or false
The equation -2x2-8x = 10is rewritten in the form of -2(x-p)2+q = 0. What is the value of q?
Answer:
q = -2
Step-by-step explanation:
-2x²-8x = 10 (divide both sides by -2)
x² + 4x = -5 (Apply completing the square method)
x² + 4x + (4/2)²= -5 + (4/2)²
x² + 4x + 2²= -5 + 2² (reduce left hand side using a²+2ab+b² = (a+b)² )
(x+2)² = -5 +4
(x+2)² = -1
(x+2)² + 1 = 0 (multiply both sides by -2)
(-2)(x+2)² + 1 (-2) = 0
-2[x - (-2)]² + (-2) = 0 ---> compare this with -2(x-p)² + q = 0
We can see that p = 2 and q = -2
The value of 'q' in the rearranged form of the given quadratic equation -2(x-p)²+q = 0 is -6. This is obtained by completing the square and comparing the equations.
Explanation:Given the quadratic equation -2x² -8x = 10, it's rearranged to the form -2(x-p)²+q = 0. The objective is to find the value of 'q'.
To achieve this, you first need to rewrite the given equation -2x² -8x - 10 = 0 in the form -2(x-h)²+k = 0. This is called completing the square. The 'h' value here is equal to -b/2a, where 'b' is the coefficient of 'x' and 'a' is the coefficient of x². In this equation, a is -2 and b is -8 so h=(-(-8)/(2×(-2))=8/4=2.
Substituting h into the equation, you have -2(x-2)²+k=0. Now expand and simplify to get -2x²+8x-4+k=0. Comparing this with the original equation -2x² -8x -10 = 0, you can see that 'k' is equal to -10+4=-6, which is the 'q' value in the form -2(x-p)²+q = 0. So, the value of 'q' is -6.
Learn more about Quadratic Equations here:https://brainly.com/question/30098550
#SPJ2
Explain how to multiply a monomial and a polynomial that is not monomial. Give examples .
Answer:
See below.
Step-by-step explanation:
To multiply a monomil by a polynomial, multiply the monomial by each term of the polynomial.
Example: Multiply 3x^2 by 4x^2 + 5x - 2
3x^2(4x^2 + 5x - 2) =
= 3x^2 * 4x^2 + 3x^2 * 5x + 3x^2 * (-2)
= 12x^4 + 15x^3 - 6x^2
To multiply a monomial and a polynomial that is not monomial, distribute the monomial term to each term of the polynomial, and then simplify the resulting expression by combining like terms.
Explanation:To multiply a monomial and a polynomial that is not monomial, distribute the monomial term to each term of the polynomial, and then simplify the resulting expression by combining like terms.
For example, let's multiply the monomial 3x^2 by the polynomial 4x^3 + 2x - 1:
Multiply 3x^2 by 4x^3, which gives 12x^5. Multiply 3x^2 by 2x, which gives 6x^3. Multiply 3x^2 by -1, which gives -3x^2. Combine these terms: 12x^5 + 6x^3 - 3x^2. Learn more about monomial and a polynomial here:https://brainly.com/question/35584608
#SPJ2
In △ABC, m∠A=15°, a=9, and b=12. Find c to the nearest tenth.
Answer:
=20.0
Step-by-step explanation:
We can first find the angle B using the sine rule as follows:
a/Sin A=b/Sin B
9/Sin 15=12/ Sin B
Sin B= (12 Sin 15)/9
=0.345
B=Sin⁻¹ 0.345
=20.18°
We then find C by using the summation of the interior angles of a triangle.
C=180-(20.18+15)
=144.82
Finding the length of c:
a/Sin A= c/ Sin C
9/Sin 15=c/Sin 144.82
c=(9 Sin 144.82)Sin 15
=20.0
Answer:
20.0 unit ( approx )
Step-by-step explanation:
Here,
ABC is a triangle in which,
m∠A=15°, a=9, and b=12,
By the law of sine,
[tex]\frac{sin A}{a}=\frac{sin B}{b}=\frac{sin C}{c}----(1)[/tex]
[tex]\frac{sin A}{a}=\frac{sin B}{b}[/tex]
[tex]\implies sin B=\frac{b sin A}{a}[/tex]
By substituting the values,
[tex]\implies sin B=\frac{12\times sin 15^{\circ}}{9}\approx 0.3451[/tex]
[tex]\implies B \approx 20.19^{\circ}[/tex]
Now, by the property of triangle,
m∠A + m∠B+ m∠C = 180°
⇒ m∠C = 180° - 15° - 20.19° = 144.81°,
By the equation (1),
[tex]c=\frac{b sin C}{sin B}=\frac{12\times sin 144.81^{\circ}}{sin 20.19^{\circ}}=20.0370532419\approx 20.0[/tex]
The equation of the graphed line is 2x - y =-6
What is the x-intercept of the graph?
-3,-2,2,6
PLEASE ANDWER ASAP
Answer:
The x intercept = -3
Step-by-step explanation:
The x intercept is where it crosses the x axis.
Looking at the graph, it crosses at x =-3
Using the equation, we set y=0 and solve for x
2x-y =-6
2x -0 =-6
2x = -6
Divide by 2
2x/2 =-6/2
x=-3
Answer: A
Step-by-step explanation:
Edgen 2023
prescription for marilyn jones piroxicam 20 mg capsule take 1 capsule 2 times a day how many milligrams mg will marilyn take of the Piroxicam in 90 days
Answer:
she will be taking 3600 mgs. in 90 days
Step-by-step explanation:
if she is taking a 20 mgs. twice a day that will make it 40 mgs. a day. If she takes it for 90 days
you will multiply 90 by 40
so
90
x40
= 3600 mgs. in 90 days
Answer:
3600 mg
Step-by-step explanation:
She takes 1 capsule 2 times a day
2* 20 mg = 40 mg
She takes 40 mg a day
She takes them for 90 days
40 mg a day for 90 days
40*90
3600 mg
Which expression is equivalent to 10x^2y + 25x^2?
A)5x^2(2y + 5)
B)5x^2y(5 + 20y)
C)10xy(x + 15y)
D)10x^2(y + 25)
Answer:
[tex]\large\boxed{A)\ 5x^2(2y+5)}[/tex]
Step-by-step explanation:
[tex]10x^2y+25x^2=(5x^2)(2y)+(5x^2)(5)\qquad\text{distributive}\\\\=5x^2(2y+5)[/tex]
The value of equivalent expression is,
⇒ 5x² (2y + 5)
We know that;
Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Here, Given that;
The expression is,
⇒ 10x²y + 25x²
Now, We can simplify the expression as;
⇒ 10x²y + 25x²
⇒ 2×5x²y + 5×5x²
⇒ 5x² (2y + 5)
Thus, The value of equivalent expression is,
⇒ 5x² (2y + 5)
Learn more about the mathematical expression visit:
brainly.com/question/1859113
#SPJ7
What is absolute value?
Answer:
Absolute value means the distance between a number and 0.
Examples:
The absolute value of -7 is 7.
The absolute value of 5 is 5.
Key Concepts:
The absolute value sign is |x|, where x is any real number.
The absolute value removes any negative sign in front of a number.
Absolute value is an important math concept to understand. To represent the absolute value of a number, we use a vertical bar on either side of the number. Absolute value means "distance from zero" on a number line. Let's try an example to understand how absolute value works.
What is the absolute value of 4 and -4?
To find the absolute value of 4, we know that 4 is 4 units from zero on a number line. Therefore, the absolute value of 4 is 4.
For the absolute value of -4, we know that -4 is also 4 units from zero on the number line. Therefore, the absolute value of -4 is also 4.
Another way that I like to think about absolute value is no matter what number you have inside the absolute value, the result will always be positive. In other words, the absolute value of any number is the positive version of that number.
If X plus 5 equals 8, then what is X?
Answer:
X plus 5 equals 8, then whats is X. The answer would be X = 3
Step-by-step explanation: Hope it helps
Answer:
x = 3Step-by-step explanation:
[tex]x+5=8\qquad\text{subtract 5 from both sides}\\\\x+5-5=8-5\\\\x=3\\\\Check:\\\\3+5=8\qquad CORRECT :)[/tex]
Which part of the ear carries sound messages to the brain?
eardrum
bones of the middle ear
ear canal
auditory nerve
Answer:
auditory nerve
Step-by-step explanation:
the auditory nerve carries sound signals to the brain. The cochlea picks up sound waves and makes nerve signals.
Answer:
The auditory nerve
Step-by-step explanation:
What is 0.03 (with the 3 repeating)/0.03 (with both the 0 and the 3 repeating) Express your answer as a mixed number.
[tex]0.0\overline{3}=\dfrac{1}{30}\\0.\overline{03}=\dfrac{1}{33}\\\\\dfrac{0.0\overline{3}}{0.\overline{03}}=\dfrac{\dfrac{1}{30}}{\dfrac{1}{33}}=\dfrac{1}{30}\cdot33=\dfrac{11}{10}=1\dfrac{1}{10}[/tex]
There are 6 students participating in a poetry contest, in how many ways can the students who go first and second in the bee be chosen?
Answer:
There are are 30 possible ways for the 6 students to be ranked 1st and 2nd
Step-by-step explanation:
There are 6 students, and any of them could receive first place. Therefore, there are 6 possibilities for first place.
A student cannot receive first and second place, so the student who won first place cannot also win second place. Therefore, there are only 5 students who could win second place.
We can multiply these two possibilities to find the number of possible rankings of 1st and 2nd
6*5=30
There are are 30 possible ways for the 6 students to be ranked 1st and 2nd....
Graph -3x + 9y = -27
Answer:
So the x-intercept is (9,0) and the y-intercept is (0,-3).
So I'm going to graph both points and connect them with a straight-edge.
Step-by-step explanation:
I would graph this using it's x- and y-intercepts.
To find the x-intercept, set y=0.
-3x+9(0)=-27
-3x+0=-27
-3x=-27
Divide both sides by -3:
x=9
To find the y-intercept, set x=0:
-3(0)+9y=-27
0 +9y=-27
9y=-27
Divide both sides by 9:
y=-3
So the x-intercept is (9,0) and the y-intercept is (0,-3).
So I'm going to graph both points and connect them with a straight-edge.
Select all the correct answers.
GroGain and FolliclePlus are hair regrowth systems. Each company claims that the application of their product will cause hair regrowth
for balding men. A barber decided to test each company's claim. He randomly selected 30 of his customers who had similar balding
issues and asked 15 of them to use GroGain and 15 of them to use FolliclePlus.
After observing the men for six months, the barber reported that, on average, those who used GroGain had a 20% increase in hair
regrowth and those who used FolliclePlus had a 10% increase in hair regrowth.
Which of the following statements are true?
FolliclePlus is the more effective hair regrowth system because it yielded a greater hair
regrowth increase percentage.
O
GroGain is the more effective hair regrowth system because it yielded a lower hair
"regrowth increase percentage.
GroGain is the more effective hair regrowth system because it yielded a greater hair
regrowth increase percentage.
FolliclePlus's claim is true.
FolliclePlus is the more effective hair regrowth system.
GroGain's claim is true.
Answer:
GroGain is the more effective hair regrowth system because it yielded a greater hair
Step-by-step explanation:
Answer
FolliclePlus's claim is true
GroGrain's claim is true
GroGrain is the more effective hair regrowth system because it yielded a greater hair growth increase precentage
Step-by-step explanation:
PLATO
One angle measure in an acute isosceles triangle is 20°. What is the measure of one of the other angles?
80°
20°
140°
160°
Answer:
Option 2) 20°
Step-by-step explanation:
Step 1: Write relevant properties of triangle.
All 3 sides of a triangle are equal to 180 degrees.
In an isosceles triangle, 2 sides and 2 angles are same.
Step 2: Calculate another angles
Since it is an isosceles triangle, two sides will be same therefore, 2 angles will be same.
Angle 1 = Angle 2 = 20 degrees (because isosceles triangle)
Therefore, 20° is the measure of one of the other angles.
Option 2
!!
Answer: FIRST OPTION.
Step-by-step explanation:
It is important to remember that an Acute Isosceles triangle has two congruent sides and all its angles measure less than 90 degrees. Then, the third option and the the fourth option are not one of the other angles.
You know that the sum of the interior angles of a triangle is 180 degrees.
Then, let be "x" one the other angles, let's check the first option:
[tex]80\°+20\°+x=180\°\\x=80\°[/tex]
Since [tex]80\°<90\°[/tex], the angle provided in the first option is one of the other angles.
Let's check the second option:
[tex]20\°+20\°+x=180\°\\x=140\°[/tex]
Since [tex]140\°>90\°[/tex], the angle provided in the second option is not one of the other angles.
What is the solution of the system of equations? -y+3x=6 y=-6x+12
Answer:
x = 2
y = 0
Step-by-step explanation:
We can solve using substitution, substitute y in the first equation with the second equation:
-(-6x + 12) + 3x = 6
Distribute the negative sign:
6x - 12 + 3x = 6
Combine like terms:
9x - 12 = 6
Isolate the variable and solve for x by adding 12 in both sides:
9x = 18
x = 2
Substitute 2 with x in any equation to find the value of y:
-y + 3(2) = 6
-y + 6 = 6
Subtract 6 in both sides to isolate the variable:
-y = 0
0/-1 = 0
y = 0
Our answer would be x = 2 and y = 0
Answer:
(2,0)
Step-by-step explanation:
I'm going to use substitution since one of the variables in one of the equation is already solved for.
-y+3x=6
y=-6x+12
I'm going to replace the first y with the second y which is (-6x+12).
This gives me:
-(-6x+12)+3x=6
Distribute:
6x-12+3x=6
Combine like terms:
9x-12=6
Add 12 on both sides:
9x=18
Divide both sides by 9:
x=2
If x=2 and y=-6x+12, then y=-6(2)+12=-12+12=0.
The solution (the intersection) is (2,0).
PLEASE HELP
Confirm that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.
f(x) = x3 + 4 and g(x) = Cube root of quantity x minus four.
any other details you could give me ?
It is proved that f and g are inverses by showing that f(g(x)) = x and g(f(x)) = x.
What are inverse function?
An inverse function is a function that returns the original value for which a function has given the output.
How to confirm that f and g are inverses ?According to the problem,
f(x) = x³ + 4 g(x) = [tex]\sqrt[3]{x-4}[/tex]Now, f(g(x)) = [tex](\sqrt[3]{x-4})^{3} + 4[/tex] = x
g(f(x)) = [tex]\sqrt[3]{x^{3}+4 -4}[/tex] = x
Thus it is proved that f and g are inverse functions.
Find more about "Inverse Functions" here: https://brainly.com/question/1144043
#SPJ2
What is the average rate of change for the sequence shown below? coordinate plane showing the points 1, 4; 2, 2.5; 3, 1; and 4, negative 0.5
Answer:
-1.5
Step-by-step explanation:
So your set of points I believe is:
(1,4)
(2,2.5)
(3,1)
(4,-0.5)
You are asked to find the average rate of change. This just means find the slope.
So you can make sure the slope is the same per pair of points.
So I like to find the slope by lining two points up vertically and subtracting vertically then put 2nd difference over 1st difference.
(2 , 2.5)
-( 1 , 4)
----------------
1, -1.5
So the slope is -1.5/1 or just -1.5.
Check another pair:
(3 , 1 )
- (2 ,2.5)
------------
1 , -1.5
So the slope is -1.5/1 or just -1.5.
Check one more:
(4 , -.5)
-(3 , 1)
-----------
1, -1.5
So the slope is -1.5 or just -1.5
So the average rate of change is -1.5.
What is the value of n in the equation
1/2(n-1) - 3 = 3 - (2n + 3)?
Hey there! :)
1/2(n - 1) - 3 = 3 - (2n + 3)
Simplify.
1/2n - 1/2 - 3 = 3 - 2n - 3
Add like terms.
1/2n - 3 1/2 = -2n
Add 3 1/2 to both sides.
1/2n = -2n + 3 1/2
Then, add 2n to both sides.
1/2n + 2n = 3 1/2
Simplify!
2 1/2n = 3 1/2
Make everything into improper fractions!
5/2n = 7/2
Multiply everything by 2 to get rid of the denominators.
5/2n × 2 = 7/2 × 2
Simplify!
5n = 7
Divide both sides by 5.
n = 7/5
Hope this helped! :)
Answer:
[tex]\frac{7}{5} = n[/tex]
Step-by-step explanation:
[tex] \frac{1}{2} (n - 1) - 3 = 3 - (2n + 3) \\ [/tex]
Solve the brackets.
[tex] \frac{n}{2} - \frac{1}{2} - 3 = 3 - 2n - 3 \\ [/tex]
Make the denominator the same to solve the fractions.
[tex] \frac{n}{2} - \frac{1}{2} - \frac{3 \times 2}{1 \times 2} = 3 - 2n - 3 \\ [/tex]
Combine like terms.
[tex] \frac{n}{2} - \frac{1}{2} - \frac{6}{2} = - 2n \\ \\ \frac{n - 7}{2} = - 2n \: \: \: \: \: \: \: \: [/tex]
Use cross multiplication to solve for n.
[tex]n - 7 = - 4n \\ \\ - 7 = - 4n - n \\ \\ - 7 = - 5n \: \: \: \: \: \: \\ \\ \frac{ - 7}{ - 5} = \frac{ - 5n}{ - 5} \: \: \: \: \\ \\ \frac{7}{5} = n \: \: \: \: \: \: \: [/tex]
through: (2,2), parallel to y=x+42)
Answer:
y=x
Step-by-step explanation:
We want a line parallel to y =x+42
The slope of y =x+42 is 1
Parallel lines have the same slope
We have the slope m=1 and a point (2,2)
We can use point slope form to write a line
y-y1 = m(x-x1)
y-2 = 1(x-2) point slope form
Changing to slope intercept form
y-2 = x-2
Add 2 to each side
y-2+2 = x-2+2
y=x
The line parallel to y = x + 42 travels through (2,2) can be represented by the equation y = x. This conclusion is based on the principles of line equations in a two-dimensional space, with slopes determining the parallelism of lines.
Explanation:The subject of the question pertains to the formula of a line in a two-dimensional space. Specifically, you're asked to find a line that passes through the point (2,2) and is parallel to the line described by the equation y = x + 42.
In a standard equation of a line, y = mx + b, 'm' represents the slope of the line and 'b' indicates the y-intercept. Two lines are parallel if they have the same slope. Bearing this in mind, as the line y = x + 42 has a slope of 1 (since 1 is the coefficient of 'x'), the required line would also possess a slope of 1.
Substituting the point coordinates (2,2) into the equation y = mx + b (replacing 'm' with 1), gives us 2 = 2 + b. Solving for 'b', we find that it equals zero. Hence, the equation of a line parallel to y = x + 42 passing through the point (2,2) is y = x.
Learn more about Line Equation here:https://brainly.com/question/21511618
#SPJ3
What is the product of Seven square root eight times four square root five? Simplify your answer. Twenty eight radical ten Fifty six radical two Fifty six radical ten Two hundred eighty radical four
Answer:
56√10.
Step-by-step explanation:
7√8 * 4√5
= 28 √40
= 28 √4√10
= 28 * 2√10
= 56√10.
Answer:
56[tex]\sqrt{10}[/tex]
Step-by-step explanation:
Using the rule of radicals
[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex]
Given
7[tex]\sqrt{8}[/tex] × 4[tex]\sqrt{5}[/tex]
= 7 × 4 × [tex]\sqrt{8(5)}[/tex]
= 28 × [tex]\sqrt{40}[/tex]
= 28 × [tex]\sqrt{4(10)}[/tex]
= 28 × [tex]\sqrt{4}[/tex] × [tex]\sqrt{10}[/tex]
= 28 × 2 × [tex]\sqrt{10}[/tex]
= 56[tex]\sqrt{10}[/tex]
HELPPP MEEEEEE PLEASE
Step-by-step explanation:
We arrange numbers in ascending order
Range - numbers appearing (without repetition)
Median - middle value
Mean - the sum of the numbers divided by the number of items
Mode - the value that appears most often.
[tex]\bold{Q4.}\\\\22,\ 36,\ 39,\ 39,\ 40,\ 40,\ 41,\ 42,\ 45,\ 46,\ 46,\ 49\\\\\bold{Range:}\ 22,\ 36,\ 39,\ 40,\ 41,\ 42,\ 45,\ 46,\ 49\\\\\bold{Median:}\ 40,\ 41\to\dfrac{40+41}{2}=40.5\\\\\bold{Mean:}\ \dfrac{22+36+39+39+40+40+41+42+45+46+46+49}{12}=40\dfrac{5}{12}\\\\\bold{Mode:}\ 39,\ 40\ and\ 46[/tex]
[tex]\bold{Q5.}\\\\79,\ 83,\ 84,\ 86,\ 86,\ 90,\ 94\\\\\bold{Range:}\ 79,\ 83,\ 84,\ 86,\ 90,\ 94\\\\\bold{Median}:\ 86\\\\\bold{Mean:}\ \dfrac{79+83+84+86+86+90+94}{7}=86\\\\\bold{Mode:}\ 86[/tex]
6.789 the digits 8 stand for
Answer:
8/100. Eight hundredths or we can write it as 8 * 10^-2.
Step-by-step explanation:
The first digits after the decimal point is tenths ( 7 tenths) and the second is hundredths, the third is thousandths.
In a geometric progression of positive terms, the 5th term is 9 times the 3rd term and the sum of the 6th and 7th terms is 972. Find the
a) common ratio
b) sum of the first 6 terms
Answer:
a) 3
b) 364
Step-by-step explanation:
A geometric sequence in explicit form is [tex]a_n=a_1 \cdot r^{n-1}[/tex] where [tex]a_1[/tex] is the first term and [tex]r[/tex] is the common ratio.
We are given:
[tex]a_5=9 \cdot a_3[/tex]
[tex]a_6+a_7=972[/tex].
What is a) r?
What is b) the sum of the first 6 terms?
So I'm going to use my first equation and use my explicit form to find those terms in terms of r:
[tex]a_1 \cdot r^4=9 \cdot a_1 \cdot r^{2}[/tex]
Divide both sides by [tex]a_1r^2[/tex]:
[tex]r^2=9[/tex]
[tex]r=\sqrt{9}[/tex]
[tex]r=3[/tex].
So part a is 3.
Now for part b).
We want to find [tex]a_1+a_2+a_3+a_4+a_5+a_6[/tex].
So far we have:
[tex]a_1=a_1[/tex]
[tex]a_2=3a_1[/tex]
[tex]a_3=3^2a_1[/tex]
[tex]a_4=3^3a_1[/tex]
[tex]a_5=3^4a_1[/tex]
[tex]a_6=3^5a_1[/tex].
We also haven't used:
[tex]a_6+a_7=972[/tex].
I'm going to find these terms in terms of r (r=3).
[tex]3^5a_1+3^6a_1=972[/tex]
[tex]243a_1+729a_1=972[/tex]
You have like terms to add:
[tex]972a_1=972[/tex]
Divide both sides by 972:
[tex]a_1=1[/tex]
The first term is 1 and the common ratio is 3.
The terms we wrote can be simplify using a substitution for the first term as 1:
[tex]a_1=a_1=1[/tex]
[tex]a_2=3a_1=3(1)=3[/tex]
[tex]a_3=3^2a_1=9(1)=9[/tex]
[tex]a_4=3^3a_1=27(1)=27[/tex]
[tex]a_5=3^4a_1=81(1)=81[/tex]
[tex]a_6=3^5a_1=243(1)=243[/tex].
Now we just need to find the sum of those six terms:
1+3+9+27+81+243=364.
ABCD is a parallelogram. Find the values of x and y. Solve for the value of z, if z=x−y.
A. -10
B. -20
C. 20
D. 30
Answer:
C
Step-by-step explanation:
Parallel and opposite sides of a parallelogram are equal. Hence, we can say:
x + 30 = 2x - 10
and
2y-10 = y +10
Solving first one, we get:
x + 30 = 2x - 10
30+10 = x
x = 40
Also
2y - 10 = y + 10
y = 10 + 10
y = 20
Now, z = x - y, so
z = 40 - 20 = 20
Answer C is right.
I can confirm that the answer is right.
Parallelograms have equal opposite sides. Do the math:
x - y = z
40 - 20 = 20
z = 20
The cost of a book was decreased from 60 to 50 by what percent the price decrased with solution
Answer:
The price decreased by 16 1/3%, or approximately 16.3%
Step-by-step explanation:
Use the formula for percent change. If the answer is negative, it is a percent decrease. if the answer is positive, it is a percent increase.
percent change = (new price - old price)/(old price) * 100%
In this case, use:
new price = 50
old price = 60
percent change = (new price - old price)/(old price) * 100%
percent change = (50 - 60)/60 * 100%
percent change = -10/60 * 100%
percent change = -1/6 * 100%
percent change = -100/6% = -50/3% = -16 1/3%
The price decreased by 16 1/3%, or approximately 16.3%